VD_FINDINFO Réc-civile / 2015 / 18 vom 10. Juni 2015 - VD Tribunal cantonal (2015)
RÉCUSATION, DROIT À UNE AUTORITÉ INDÉPENDANTE ET IMPARTIALE, REJET DE LA DEMANDE | 6 ROTC, 47 al. 1 let. f CPC (CH), 47 CPC (CH), 49 al. 1 CPC (CH), 49 CPC (CH), 8a al. 5 CDPJ